Inter-block 4-erasure-correcting coding scheme for real-time bulk data transfer - Gang CHEN; Jun-feng ZHU; Shi-le ZHANG; Bai-feng WU (Tongxin xuebao)
Most of the existing erasure-correcting codes were limited by encoding/decoding complexities and encoded data size.They were not suitable for use in the real-time applications that orient bulk data based on blocks or packages.Therefore,a novel inter-block 4-erasure-correcting coding scheme for real-time bulk data transfer was presented.Based on single parity-check codes incorporated with the features of GF(2＜sup＞8＜/sup＞)field in finite field,the present coding scheme could tolerate simultaneous failures of four blocks with only four redundancy blocks for a group of continuous data.Meanwhile,its encoding/decoding complexities had linear relationship with respect to the size of data blocks and it supported arbitrary size of data.Furthermore,it was proved to have MDS property,thus achieving optimal erasure-correcting capability with the same redundancy information.Theoretical and experimental analysis showed that the present coding scheme could code with 27 continuous data blocks at most.